The Babri Mosque and Hindu Extremists Movements - Abdul Majid (Journal of Political Studies, 2015)
India’s constitution upholds secularism and respect for religious diversity. However, there is a counter narrative of Hindu India. This means that India’s identity should be defined on extremist Hindu religious lines and that all religious minorities should accept this identity. This point of view is propagated by Hindu hard line groups. These groups claimed that the Babri Mosque was originally the birth place of RAM. Therefore, it should be demolished and a full Ram Mandir be established. The Congress Party Government could not control them and they demolished the Babri Mosque on December 6, 1992. These Hindu extremist group identify with the BJP that ruled India in 1999- 2004 and from May 2014 to the present. As the Modi Government in India indirectly supports Hindu hard line ideology these groups have used violence or threat of violence against the Muslims and other religious minorities who are citizens of India.